Analisis Volume Minyak Gaharu Tipe Aquilaria malaccensis L. pada Proses Penyulingan Minyak Gaharu - Herliani Herliani (Universitas Sebelas Maret, 2018)
The agarwood tree is one of the plants of the Spermatophyta Division, the Angiospermae subdivision, and the Class Dicotyledoneae. Gaharu is one of the commodities of Non-Wood Forest Products which has very high and high selling value. Gaharu are grouped into 3 (three) sortimen of gaharu sapwood, gaharu pomegranate, and gaharu ash. Gaharu oil is an essential oil obtained by distillation process. Distillation is a process of isolating essential oil from its raw materials with the help of water vapor, where oil and water do not mix. The purpose of this study is to determine whether there is a difference in the volume of gaharu oil to different types of aloes Aquilaria malaccensis L. on the process of gaharu oil distillation. The type of research used is descriptive analysis, using a qualitative approach. The population used in this research is gaharu type Aquilaria malaccensis L. The sample used in this research is gaharu oil produced from the distillation process. The results showed that the volume of oil produced from aloe species Aquilaria malaccensis L. with type kemedengan as much as 3.5 grams and gubal type as much as 11.1 gr. So it can be concluded that the different types of gaharu wood used in the distillation process can affect the volume of gaharu oil produced from each type of gaharu wood, in addition that determines whether or not the oil produced from the distillation process is the texture of the raw materials used and the number sap or resin contained from the wood itself.